If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k(k) = y Multiply k * k k2 = y Solving k2 = y Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Simplifying k2 = y Combine like terms: y + -1y = 0 k2 + -1y = 0 The solution to this equation could not be determined.
| 5x=4+-.1y | | 0=56+7x | | 0.16(18x+30)-8x= | | 4x-7w= | | 13s-234=3s-14 | | 10a-2b=-26 | | 2(9+x)=-15(4+x) | | -6=h/18 | | (7x-6)=6-7x | | 5x+17=5x+98 | | X^3-48=4x | | 30+8n=4(2n+7) | | x=2x-73 | | m+1.89=6.519 | | 7(x+4)=3(x+2) | | -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) | | u=4(2n+33)+5(n+1) | | 2(3z+1)-(2-6)= | | f(0.03)=3x^3-2x^2+6x-4 | | a=(5x-3)(x+2)(2x+3)(3x-2) |